Law Enforcement at Indonesian Waters: Bakamla vs. Sea and Coast Guard - Puspitawati, Dhiana; Hadiyantina, Shinta; Susanto, Fransisca Ayulistya; Apriyanti, Nurul (Indonesian Journal of International Law, 2020)
This paper aims to analyze Indonesian laws regarding law enforcement in Indonesian waters. Specifically, it analyzes the authority of Badan Keamanan Laut (BAKAMLA) and Indonesian Sea and Coast Guard under the Indonesian Act Number 32 the Year 2014 on the Ocean Affairs Act and Indonesian Act Number 17 the Year 2008 on Navigation Act, respectively. It is argued that the state’s sovereignty over the ocean differs from the state’s sovereignty over the land territory. This is because according to the United Nations Convention on the Law of the Sea 1982 (UNCLOS 1982), the state’s ocean territory is divided into various maritime zones, over which different regimes applied. It is submitted that the farther ocean space is from the land territory, the sovereignty of the coastal state is lessened. Thus, different treatment, especially concerning law enforcement is needed this paper recommends a model for law enforcement at sea, which considers different regimes over different maritime zones as provided within the UNCLOS 1982. It is submitted that while it is fine to have more than one institution having the authority of law enforcement at sea, the extent of such authorization should be clarified.